Analisis Pengaruh Modal Dan Pengalaman Kerja Terhadap Produktivitas Dan Pendapatan Peternak Babi Di Kabupaten Bangli - Putra, Ida Bagus Gede Yogi Jenana; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 8, No. 4, April 2019, pp (703-940), 2019)
ABSTRACT The purpose of this study was to analyze 1) direct influence of capital and work experience on productivity, 2) direct influence of capital, work experience and productivity on income, 3) the influence of capital and work experience on income indirectly through productivity in pig farmers in the Regency Bangli. This research was conducted in Bangli District with respondents of pig farmers who have pigs> 10 head. The sample in this study amounted to 64 respondents. The data analysis technique used is path analysis / path analysis. Based on the results of the study, it was concluded that capital and work experience had a positive and significant effect on the productivity of pig farmers in Bangli Regency. Capital, work experience and productivity have a positive and significant impact on the income of pig farmers in Bangli Regency. Capital and work experience have an indirect influence through productivity on the income of pig farmers in Bangli Regency. Suggestions from this study pig farmers must increase their capital and work experience to increase their productivity and opinion. Keywords: capital, work experience, productivity and income